Choosing Post-Secondary Vocational Education Pathways: Narratives of Young Adults with Previous System Involvement. - Collins, Mary Elizabeth; Augsberger, Astraea; Mohanty, Sruti (Child & Adolescent Social Work Journal, 2026)
Extensive policy and practice attention aims to support young people as they seek to achieve educational and career goals yet there are widely varying trajectories toward these goals that reflect individual preferences and social inequalities. This study reports findings from qualitative interviews with 16 young adults currently enrolled in a primarily vocational pathway at a community college and who had prior involvement with child welfare, juvenile justice or mental health systems. Using a narrative approach, respondents described their career and educational pathways including their current status, antecedents, and future trajectory. Key factors that have impacted their pathway include their initial vocational interests, messages from within their social networks, and impacts of work and family life on educational goals. Study results have implications for better supporting young people with system involvement to identify and achieve their educational and career goals.